Chapter 19 Subjects, topics and the interpretation of pro - Rizzi, Luigi (De Gruyter, 2018)
In this paper I would like to address the classical issue of the similarities and differences between subject and topic positions. In doing so, I will build on seminal work by Andrea Calabrese, particularly Calabrese (1986) on pronominal interpretation. This paper, as well as other contributions on prosody, syntax and information structure (Calabrese 1982, 1992) anticipated and inspired a view of the syntax-pragmatics interface which turned out to be of crucial importance for cartographic projects.